Biological Potential of Homo- and Heteronuclear Complexes of Iminodiacetic Acid - Iqra Batool; Amina Iqbal; Syeda Mona Hassan; Shabbir Hussain; Khurram Shahzad Munawar; Suman Iftikhar; Muhammad Hashir Khalid; Sabahat Asghar (RADS Journal of Biological Research & Applied Science)
Background: Natural ligands containing the carboxylate group have been broadly utilized in many coordination complexes because of their simple manufacturing strategies, magnificent chelation properties, and biological potential. The carboxylate ligands may bind to the metal atoms in a variety of coordination modes which include monodentate/bidentate/chelating modes and may result in the formation of homo- and heterobimetallic complexes.